How Great Is the Level of Youth Cultural Sensitivity? A Multicultural Education from One Ethnic in Indonesia. (25th June 2022) - Harmi, Hendra; Ramdhani, Muhammad Iqbal; Amalia, Shynta; Apriani, Eka; Syafryadin, Syafryadin; Supardan, Dadan; Zarin, Ismat
Abstract : Indonesia is a multiethnic and cosmopolitan country. To realize a multicultural society, the variety of the Indonesian nation is employed as a feature, as the Indonesian nation's identity. Different cultures complement each other, do not stand alone, and are even capable of adapting (flexibly) to each other in the arena of daily life. Musi Rawas Utara is one of the regencies in South Sumatra Province, Indonesia, with a diversified community in terms of religion and race. Cultural, religious, political ambitions, economic divisions, and educational distinctions are among the most widely felt throughout Indonesia, particularly in the Musi Rawas region. The goal of this study was to look at the intercultural understanding of ethnic youngsters in the Musi Rawas area. The demographics of this study include all youth ethnic groups in the Musi Rawas area. A purposive sample was used, with 75 participants drawn from three villages in Musi Rawas Utara Regency, South Sumatra. A nontest strategy was used to collect data in the form of a questionnaire. The research tool employed in this study was a questionnaire with four response options: strongly agree, agree, disagree, and strongly disagree. In this sense, it may be argued that the youth ethnic groups, Orang Rimba, in Musi Rawas Utara, have a good understanding of multiculturalism.